A Dual‐Modal SERS/Fluorescence Gold Nanoparticle Probe for Mitochondrial Imaging. Issue 5 (31st January 2017) - Eling, Charlotte J.; Price, Thomas W.; Marshall, Addison R. L.; Narda Viscomi, Francesco; Robinson, Peter; Firth, George; Adawi, Ali M.; Bouillard, Jean‐Sebastien G.; Stasiuk, Graeme J.
Abstract: A novel SERS/fluorescent multimodal imaging probe for mitochondria has been synthesised using 12 nm diameter gold nanoparticles (AuNP) surface functionalised with a rhodamine thiol derivative ligand. The normal pH‐dependent fluorescence of the rhodamine‐based ligand is inversed when it is conjugated with the AuNP and higher emission intensity is observed at basic pH. This switch correlates to a pKa at pH 6.62, which makes it an ideal candidate for a pH‐sensitive imaging probe in the biological range (pH 6.5–7.4). The observed pH sensitivity of the ligand when attached to the AuNP is thought to be due to the formation of a spirolactam ring, going from positively charged (+18 mV) to negatively charged (−60 mV) as the pH is changed from acidic to basic. Additionally, conjugation of the ligand to the AuNP serves to enhance the Raman signal of the rhodamine ligand through surface‐enhanced Raman scattering (SERS). Confocal microscopy has shown that the probe enters HEK293 (kidney), A2780 (ovarian cancer) and Min6 (pancreatic beta) cells within an hour and a half incubation time. The probe was shown to localise in the mitochondria, thus providing a novel pH‐dependent SERS/fluorescent multimodal imaging probe for mitochondria. Abstract : Go for gold ! Gold nanoparticles that were functionalised with a thiol rhodamine derivative serve as a multimodal probe for cellular imaging. The normal pH‐dependent fluorescence of rhodamine is inversed, with higher emission observed at high pH. The probe was shown to localise in the mitochondria.